PHENOTYPIC AND MOLECULAR IDENTIFICATION OF NONMUTANS STREPTOCOCCI ORGANISMS RECOVERED ON MITIS-SALIVARIUS BACITRACIN AGAR FROM CARIES ACTIVE SUBJECTS - KHALID IMRAN; R. SENTHILKUMAR (International Journal of Pharma and Bio Sciences, 2014)
Dental caries is one of the most common oral infectious disease affecting humans worldwide and Mutans Streptococci (MS) have been implicated as major cariogenic bacteria. The “low-pH non-Mutans Streptococci Organisms (non-MSO) have been identified as atypical strains in caries plaque samples, in the absence of MS group. The non-MSO usually competes with MS group for colonizing on the tooth surface. The objective of the present study was to isolate and identify the non-MSO recovered on MitisSalivarius Bacitracin (MSB) agar from caries active subjects. Dental plaque samples were collected from caries active subjects and cultured on MSB agar. The bacteria grown on MSB agar were subjected to biochemical tests and 16S rDNA identification. Among 38 subjects, 4 subjects were positive for non-MSO, which were identified as Streptococcus anginosus (03) and Streptococcus sanguinis (01). The detection of non-MSO in caries active subjects, confirmed their involvement in the infection which may support “Nonspecific plaque hypothesis” of caries formation.